Exploration of Indole-3-Acetic Acid (IAA)-Producing Rhizosphere Fungi in Environmentally Friendly And Conventional Cabbage Fields at The UB Agrotechnopark - Hadameon, Bagas; Rachmawati, Rina; Sandy, Yohana Avelia (Journal of Tropical Plant Protection, 2023)
Soil is a habitat for many types of microbes that have a role in maintaining soil nutrition, and most of them grow around plant roots. Factors that are quite influential in the growth process are the hormone auxin, which has a role in stem bending and stimulates differentiation. This study aimed to obtain a genus of IAA hormone-producing rhizosphere fungi (Indole-3-Acetic Acid) and determine the effect of environmentally friendly and conventional land cultivation on the diversity of IAA hormone-producing fungi at Agrotechnopark UB Cangar Garden. Fungi isolates were cultured on Potato Dextrose Agar (PDA) and Potato Dextrose Broth (PDB) media enriched with tryptophan as a precursor to form IAA. IAA measurements were carried out qualitatively by adding the Salkowski reagent and quantitatively by measuring the absorbance. As many as 10 rhizosphere fungal isolates were obtained from environmentally friendly land and 8 fungal isolates from conventional land, which produced IAA hormones. The fungal genera obtained included Acremonium, Aspergillus, Colletotrichum, Fusarium, Penicillium, and Trichoderma. Environmentally friendly cabbage fields (average: 283.8 ppm) showed higher yields than conventional fields (average: 140.9 ppm) in producing IAA hormones. There was a correlation between soil pH and organic matter on fungal diversity, with a correlation value of 0.878. The diversity index value of rhizosphere fungi was 1.359; the evenness index was 0.845, and the dominance index was 0.302 on environmentally friendly land. The diversity index value of rhizosphere fungi was 1.213; the evenness index was 0.875, and the dominance index was 0.344 on conventional land.